Does forest loss and fragmentation reduce woodpecker-associated ecosystem functions? - Kazuma Yasuda; Daiki Kato; Shoji Naoe; Tatsuya Amano; Tetsuro Yoshikawa; Kahoko Tochigi; Shinsuke Koike (Global Ecology and Conservation)
Around the world, land-use change caused by human-activity threatens biodiversity, which often results in forest loss and fragmentation, and the loss of forest biodiversity. Forest loss and fragmentation resulting from plantations can have a substantial impact on bird communities because plantations are essentially less suitable environments for bird communities than natural forests. Woodpeckers inhabiting large trees are particularly susceptible to forest loss and fragmentation. They play a critical role in the ecosystem, as they not only create tree cavities, but might also contribute to the number of tree falls. Their functions are indispensable and cannot be substituted by those of other species. A decline in woodpecker numbers due to forest loss and fragmentation is likely to change forest ecosystems in various ways. This study examined whether the fragmentation and loss of natural forests has resulted in a decline in the woodpecker population, resulting in reduced number of tree cavities, and consequently, a reduced number of tree falls. The results of this study indicate that the number of fallen trees was positively related to the number of woodpeckers through the number of tree cavities they created. In addition, forest loss, not forest fragmentation, was related to decrease in woodpecker abundance, leading to negative cascading effects on the number of tree cavities and fallen trees. Forest loss changed the woodpecker community structure by affecting the woodpecker guilds differently. Conserving large broad-leaved forests could contribute to the conservation of specific woodpecker species and their roles in the ecosystem.